Mechanical and durability performance of marine sand and seawater concrete incorporating silicomanganese slag as coarse aggregate. (10th September 2020) - Ting, Matthew Zhi Yeon; Wong, Kwong Soon; Rahman, Muhammad Ekhlasur; Selowara Joo, Meheron
Highlights: Concrete incorporated with silicomanganese (SiMn) slag, marine sand and seawater was studied. SiMn slag reduced concrete compressive and tensile strengths by 9.2% and 17.5% respectively. SiMn slag concrete exhibited comparable durability in the long term. Marine sand had advantageous effect on durability of concrete. Abstract: This experimental investigation has validated the feasibility of utilizing silicomanganese (SiMn) slag, marine sand and seawater in concrete production. Compressive and splitting tensile strengths of concrete were evaluated. Assessment was also performed on concrete durability which included water absorption, sorptivity, chloride penetration and sulphate resistance. SiMn slag was found to reduce concrete compressive and tensile strengths by 9.2% and 17.5% respectively. Nevertheless, the concrete exhibited comparable durability to conventional concrete at 90-day age, though it showed reduced value at 28-day age. The research also illustrated that marine sand improved concrete durability by at least 42.3% and 11.5% in aspect of sorptivity and chloride penetration respectively, while seawater showed little effect. More durable concrete can be produced by utilizing SiMn slag, marine sand and seawater for potential industrial application.